Role of community management services at Greenovent Ltd.: A study on How brands utilize social media engagement to enhance customer Relationship. - Kaushik, Farid-Uz-Zaman (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.